MENINGKATKAN PENDAPATAN PETANI KUTU LAK MELALUI PEMBERDAYAAN POTENSI DAERAH - Fabianus Ranta (Politeknik Pertanian Negeri Kupang, 2009)
Increase Kutu Lak Farmer Income Passes Region Potential Empowering. This watchfulness aims to find tree inang alternative successor kesambi as tree inang kutu lak that has production bigger than production that produced from tree inang kesambi in order to increase shellac availability for pharmacy industrial, cosmetics and electronic industrial. Efforts increases product seed lak, necessary pay attention utilization basis continues. if utilization basis continues membudaya and take root in society, so will whatever that be done in order to will fulfil request seed lak world will pass product increase seed lak can materialized. thereby kutu lak farmer welfare can increase to pass income enhanced from harvest result seed lak. To achieve aim meants, so in this article is elaborated about status kesambi threatened destroyed. therefore, wanted plants inang alternative successor kesambi that has physiological feature, condition grows and predicted has ability last forproduce seed lak. beside that, farmer enableness is efforts civilizings kutu lak cultivation is one of the suggestion that elaborated author to change kutu lak cultivation pattern conventionally be kutu lak cultivation based on benefit continues. Keywords: increase, kutu lak farmer income, region potential, empowering